2011
DOI: 10.1149/1.3599066
|View full text |Cite
|
Sign up to set email alerts
|

Electroless Deposition of Silver on Multiwalled Carbon Nanotubes Using Iodide Bath

Abstract: Electroless deposition of silver on multiwalled carbon nanotubes (MWCNTs) was investigated using an iodide bath. Prior to electroless deposition of silver, the MWCNTs were chemically oxidized and then pre-treated using a typical two-step method (sensitization and activation) to form catalytic palladium nuclei on the MWCNTs. Dimethylaminoborane (DMAB) was used to reduce silver ions. Electroless deposition of silver was carried out at 25 C with variation of the pH. The microstructure of the deposits was evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 30 publications
(39 reference statements)
0
11
0
Order By: Relevance
“…32,33 In the isolated Ag-Pd NPs, the Ag and Pd are completely miscible at any proportion due to the same crystallographic structure with the similar lattice parameters and no miscibility gap at any composition based on the Ag-Pd alloy phase diagram. 34 In contrast to the monometallic dewetting, the bilayer dewetting can be slightly different and indeed somewhat more complex due to the various factors such as different diffusivity, surface energies, surface segregation, alloying, lattice mismatch and stress generation-relaxation between constituent materials, etc. Therefore, the dewetting extent can be signicantly varied even at identical growth conditions such as annealing temperature, thickness and duration by the alteration of composition or sequence of individual atomic species.…”
Section: Methodsmentioning
confidence: 99%
“…32,33 In the isolated Ag-Pd NPs, the Ag and Pd are completely miscible at any proportion due to the same crystallographic structure with the similar lattice parameters and no miscibility gap at any composition based on the Ag-Pd alloy phase diagram. 34 In contrast to the monometallic dewetting, the bilayer dewetting can be slightly different and indeed somewhat more complex due to the various factors such as different diffusivity, surface energies, surface segregation, alloying, lattice mismatch and stress generation-relaxation between constituent materials, etc. Therefore, the dewetting extent can be signicantly varied even at identical growth conditions such as annealing temperature, thickness and duration by the alteration of composition or sequence of individual atomic species.…”
Section: Methodsmentioning
confidence: 99%
“…By referring some reports, 14,20,22 the multi-walled carbon nanotubes (MWCNTs) were acid treated with ultrasonication in 3:1 (volume ratio) H2SO4 aq (98wt%)/HNO3 aq (68wt%) for 6 h. The sample was filtered and washed with deionized water until the pH of the filtrate water became neutral. The filtered MWCNTs were dried for 12 h under vacuum at 120°C.…”
Section: Acid Treatment Of Carbon Nanotubesmentioning
confidence: 99%
“…They have been used to produce metal-MWCNTs composites such as Ni, Ag and Cu, which were electroplated from MWCNTs-dispersed aqueous baths. 20,21,22 Since Al cannot be electrodeposited from aqueous baths, non-aqueous baths such as organic and ionic liquid baths have been investigated. [23][24][25] However, there has been only one report about electrodeposition of Al-MWCNTs, where an ionic liquid bath was used.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of the hydrothermal treatment of CNT in mixed acid solution was investigated. Acid treatment of CNT is a widely-used method to impart hydrophilicity to CNT [29] but it has been reported that an additional dispersant should be added because it is difficult to obtain sufficient dispersibility by acid treatment alone [30]. Therefore, in this study, hydrothermal treatment of CNT was applied in a mixed acid solution, which may not require additional dispersants which may deteriorate the electrical conductivity.…”
Section: Effect Of Hydrothermal Treatment On Cntmentioning
confidence: 99%